2020
DOI: 10.14309/ctg.0000000000000189
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Recurrent Clostridioides difficile Infection in Patients With Cirrhosis

Abstract: INTRODUCTION: Clostridioides difficile infection (CDI) is common in patients with cirrhosis and is associated with poor outcomes. CDI risk factors in this population have been well characterized; however, risk factors of recurrent CDI (R-CDI) after treatment have not been explored. We sought to estimate the incidence of R-CDI and its associated risk factors in patients with cirrhosis. METHODS: We performed a cohort study of patients with cirrhosis hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The impact of these agents on CDI in cirrhosis needs to be further supported in high-quality studies. A study showed risk factors for R-CDI in cirrhosis, including Charlson Comorbidity Index and lactulose use, which is aligned with the risk factors for CDI [ 21 ] ( Figure 1 ).…”
Section: Risk Factorsmentioning
confidence: 70%
See 4 more Smart Citations
“…The impact of these agents on CDI in cirrhosis needs to be further supported in high-quality studies. A study showed risk factors for R-CDI in cirrhosis, including Charlson Comorbidity Index and lactulose use, which is aligned with the risk factors for CDI [ 21 ] ( Figure 1 ).…”
Section: Risk Factorsmentioning
confidence: 70%
“…The incidence of R-CDI in patients with cirrhosis was studied in a cohort study conducted at Indiana University Hospital from 2012 to 2016, with an 11.9% incidence of R-CDI among those hospitalized with CDI in patients with cirrhosis [ 21 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations